Formation of Rehabilitation Diagnosis in Patients with Breast Cancer at Stage I of Medical Rehabilitation: Case Report - Galina E. Ivanova; Tatyana V. Builova; Lyudmila A. Belova; Yuri D. Udalov; Viktor V. Mashin; Andrey Yu. Suvorov; Anastasia A. Kuvaiskaya (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
The article reviews the main complaints of patients with breast cancer depending on the type of antitumor treatment and defines thepeculiarities of the basic and additional sets of the International Classification of Functioning (ICF) codes.Aim. To present the clinical experience results of ICF use in making a rehabilitation diagnosis for patients with breast cancer, to discussthe issues and problems that arise when choosing domains in patients receiving various methods of treatment for this disease, to showby the example of a case report the use of ICF when forming a rehabilitation diagnosis in a patient with breast cancer after surgicaltreatment and anti-tumor drug therapy.Results and discussion. Patients who had undergone the surgical treatment, in the early postoperative period are predominantlycharacterized by: pain in the arm and shoulder joint, swelling of the arm, limited range of movement in the shoulder joint on theoperation side, increased fatigue, difficulties in self-care, irritability, and anxiety. Patients who had eceived radiation therapy complainedof skin manifestations - reddening of the skin in the area of radiation exposure and trophic ulcers, as well as complaints of numbnessof the fingers and toes, palpitations, a feeling of interruptions in the heart area, frequent changes in blood pressure, which arecharacteristic signs peripheral polyneuropathy and cardiovascular form of autonomic neuropathy. Distinctive features of patientshad being receiving anticancer medication therapy were complaints of disorders in the digestive system, hair loss. According to thecomplaints of each category of patients, the basic and additional sets of ICF were determined to make a rehabilitation diagnosis. Thecase report demonstrates the practical application of the basic and the inclusion of additional ICF sets for making a rehabilitationdiagnosis for a patient with breast cancer and determining the tactics of rehabilitative measures.Conclusion. The results of the study suggest the importance of reflecting the completeness of all domains of the ICF domains specificfor a particular patient, as the aim of rehabilitation is established on the basis of the rehabilitation diagnosis formulated by MDRTspecialists.